2022
DOI: 10.1111/aas.14169
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve‐blocks and associations with length of stay and readmissions in fast‐track total hip and knee arthroplasty

Abstract: Background: Peripheral nerve blocks (PNB) have recently been recommended in total hip (THA) and knee (TKA) arthroplasty as they may reduce pain, morphine consumption, length of stay (LOS) and complications. However, whether PNBs are associated with early discharge within an enhanced recovery protocol including multimodal analgesia is uncertain.Methods: An observational multicenter study from January to August 2017 in six Danish Arthroplasty Centers with established fast-track protocols. Prospective recording o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…5 In contrast, our study in fast-track THA and TKA with a fully implemented multimodal opioid-sparing analgesic regimen, demonstrated that the majority of patients were discharged within 1-2 days regardless of the use of PNB and with no differences in readmissions. 2 Consequently, although our study did not assess the analgesic effect of PNB's per se, our data does not support any added benefit on length of stay or readmissions with routine PNB in fasttrack THA.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…5 In contrast, our study in fast-track THA and TKA with a fully implemented multimodal opioid-sparing analgesic regimen, demonstrated that the majority of patients were discharged within 1-2 days regardless of the use of PNB and with no differences in readmissions. 2 Consequently, although our study did not assess the analgesic effect of PNB's per se, our data does not support any added benefit on length of stay or readmissions with routine PNB in fasttrack THA.…”
contrasting
confidence: 55%
“…
comment 1 on our recently published study on the use of peripheral nerveblocks and associations with length of stay and readmissions in fast-track total hip and knee arthroplasty. 2 We agree that the type and technique of peripheral nerveblocks (PNB) is important when evaluating effect on postoperative pain, opioid consumption and hospital stay and readmissions. This was why we, in contrast to most other studies on pain and opioid use, 3 made the effort to provide information on the type of applied nerve blocks and consequences in a full recovery program.
…”
mentioning
confidence: 99%
“…Dear Editor, In a recent study by Jørgensen et al 1 regarding the relationship between peripheral nerve blocks (PNBs) and length of stay and readmissions in total hip and knee arthroplasty (THA and TKA), we read with great interest the research findings. According to the authors, routine use of PNBs, such as femoral nerve block and lateral cutaneous femoral block, was not associated with early discharge or 30-day readmissions in THA.…”
Section: Fascia Iliaca Compartment Block Improves the Efficacy Of Ana...mentioning
confidence: 99%
“…To improve postoperative pain after THA, multimodal-analgesia can be implemented and opioid therapy dosage can be reduced by performing peripheral regional nerve blocks (PNB) [ 74 ]. PNB is recommended in THA as it reduces pain, allows early mobilization, and reduces morphine consumption while decreasing the risk of pain-related complications [ 75 , 76 , 77 , 78 ]. Different techniques can be adopted: femoral nerve block, sciatic nerve block, single shot, or continuous infusion [ 74 ].…”
Section: Peri-operative Optimizationmentioning
confidence: 99%
“…This technique is beneficial for patients who undergo THA because it provides sufficient postoperative analgesia, especially against immediate postoperative resting pain [ 79 , 80 ]. Its relation to LOS is, however, still debated, and therefore, its routine use should be evaluated singularly [ 75 ].…”
Section: Peri-operative Optimizationmentioning
confidence: 99%